2021
DOI: 10.1007/s10389-021-01539-5
|View full text |Cite|
|
Sign up to set email alerts
|

Perceptions and effects of COVID-19 related information in Denmark and Sweden – a web-based survey about COVID-19 and social media

Abstract: Aim Extensive COVID-19 information can generate information overload and confusion. Denmark and Sweden adopted different COVID-19 management strategies. Aim This study aimed to compare search strategies, perceptions and effects of COVID-19 information, in general and specifically in social media, in residents in Denmark and Sweden. Subject and methods Quantitative data from a sample of respondents (n = 616) from Den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…More than three-quarters (762/1003, 76%) of respondents stated that they have relied on social media at least "a little," and 59.2% (594/1003) of respondents indicated that they read information about COVID-19 on social media at least once per week. The heavy reliance on social media observed among US-based SNS users is consistent with findings from recent research conducted in various international settings, including China [19] and Europe [20].…”
Section: Discussionsupporting
confidence: 88%
“…More than three-quarters (762/1003, 76%) of respondents stated that they have relied on social media at least "a little," and 59.2% (594/1003) of respondents indicated that they read information about COVID-19 on social media at least once per week. The heavy reliance on social media observed among US-based SNS users is consistent with findings from recent research conducted in various international settings, including China [19] and Europe [20].…”
Section: Discussionsupporting
confidence: 88%
“…Facebook, Twitter, Instagram). The quantitative data has been reported in other articles (Stjernswärd et al, 2021a(Stjernswärd et al, , 2021b; Most survey questions, which focused on uses of social media (e.g. types, sources, reliability) to locate COVID-19 information and its effects on users, included a space for free text answers, where informants could freely complete/comment upon the multiple choice/Likert-type scale answers and add further reflections related to COVID-19, related information, and social media ('You are welcome to comment upon/develop your answer here').…”
Section: Data Collectionmentioning
confidence: 63%
“…The Challenger threatened and challenged the dominant medico-political strategy related to COVID-19, with resistance always being a possible consequence of any exercise of power (Foucault, 1995). Thus, depending on the national context, the different ideal types can support or oppose the national strategy and by extension challenge international recommendations (Stjernswärd et al, 2021a;Béland et al, 2020;Devlin and Connaughton, 2020). The Entertainer, however, both consolidated and challenged the medico-political strategy using humour, art, and literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the COVID-19 pandemic, the Danish and Swedish governments and public authorities did not use tailored communications based on socio-demographic characteristics [33,24]. Authorities in the two countries received critique for the lack of adaptation of communication to many immigrant groups beyond translation of messages into multiple languages [34,35]. Reaching some immigrant groups in both countries proved challenging when the COVID-19 vaccination programmes rolled out, resulting in low vaccination rates among some sub-groups of the immigrant populations in the two countries [36].…”
Section: Discussionmentioning
confidence: 99%